(untitled) (Journal of Informatics Education and Research, 2025)
This empirical study investigates the critical link between employee engagement and organizational effectiveness within retail companies. Amidst increased competition and rising employee attrition rates, Indian retail organizations are compelled to prioritize employee engagement as a strategic imperative. The research underscores the substantial impact of disengaged employees, including diminished productivity, higher turnover, and detrimental effects on organizational culture. Drawing upon data from industry surveys and academic frameworks such as the Job Demands-Resources Model, the paper explores multidimensional facets of engagement—including cognitive involvement, procedural awareness, stress resilience, and personal psychological resources like self-esteem and self-efficacy. Findings reveal that highly engaged employees display elevated commitment, teamwork, and participation, directly correlating with improved organizational performance. Conversely, organizational malpractices and personal deficiencies are identified as key disengagement drivers. The study offers actionable insights for retail organizations seeking sustainable competitive advantage through comprehensive engagement strategies.